POLICY ANALYSIS AND IMPLEMENTATION OF MUTATION AND EMPLOYEE PLACEMENTS ON PERFOMANCE AND CAREER DEVELOPMENT - Maria Ulfah; Dewi Prastiwi (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2020)
This study aims to assess the effectiveness of employee mutations and placements applied to several institutions in Indonesia. This study uses the meta-synthesis method by conducting a review of 31 previous studies listed in the research media. The results of the study found that government agencies in Indonesia had implemented mutation policies based on applicable regulations ranging from the law to local regulations on several factors, the value of improving performance and productivity, career development and promotion, to filling vacant positions. However, several studies have found that there is still corruption, collusion and nepotism, political affiliation, family connections, and close relations with superiors which causes a mismatch between the placement of employees and their competencies. Transfer of employees based on a merit system is indicated to improve performance including public services in providing information to create public sector accountability. Career development and promotion can also expand knowledge and experience to produce creative and innovative employees to support the achievement of organizational goals.